2021
DOI: 10.3389/fonc.2021.640720
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 as a Potential Biomarker for Adjunctive Metabolic Therapies in Tumor Management

Abstract: Glioblastoma (GBM) remains one of the most lethal primary brain tumors in both adult and pediatric patients. Targeting tumor metabolism has emerged as a promising-targeted therapeutic strategy for GBM and characteristically resistant GBM stem-like cells (GSCs). Neoplastic cells, especially those with high proliferative potential such as GSCs, have been shown to upregulate UCP2 as a cytoprotective mechanism in response to chronic increased reactive oxygen species (ROS) exposure. This upregulation plays a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…UCP2 expression is associated with cancer and modulates energy metabolism in response to elevated ROS levels [ 71 ]. Overexpression of UCP2 is found in leukaemia, ovarian, bladder, oesophageal, testicular, colorectal, kidney, pancreatic, lung and prostate tumours [ 72 ]. The effect of UCP2 on ATP concentrations varies according to cell type.…”
Section: Oxidative Phosphorylation and Mitochondrial Uncouplingmentioning
confidence: 99%
“…UCP2 expression is associated with cancer and modulates energy metabolism in response to elevated ROS levels [ 71 ]. Overexpression of UCP2 is found in leukaemia, ovarian, bladder, oesophageal, testicular, colorectal, kidney, pancreatic, lung and prostate tumours [ 72 ]. The effect of UCP2 on ATP concentrations varies according to cell type.…”
Section: Oxidative Phosphorylation and Mitochondrial Uncouplingmentioning
confidence: 99%
“…When UCP2 is upregulated, the opposite occurs, in that the exit of anions and protons from the matrix is facilitated. Although the mechanism by which UCP2 facilitates this proton transport is not fully understood, by allowing protons to leak across the IMM, the driving force behind ATP production through the electron transport chain is decreased, resulting in heat-energy release [ 2 , 11 , 13 ]. In addition to mitochondrial uncoupling, recent studies revealed that UCP2 plays an important role in the mitochondrial transport of C4 metabolites for NADPH production required for cancer cell growth ( Figure 1 ) [ 14 , 15 , 16 ].…”
Section: Uncoupling Protein 2 (Ucp2) and Cancermentioning
confidence: 99%
“…Additionally, this shift in metabolism has been shown to increase cell proliferation as long as the supply of glucose is unlimited. A recent study suggests that cells shut off mitochondrial cellular respiration by increasing the expression of mitochondrial uncoupling protein 2 (UCP2) in an effort to mitigate the effect of cytotoxic reactive oxygen species (ROS), thereby inducing the Warburg effect through UCP2 upregulation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crosstalk between the immune checkpoint and metabolic pathways may profoundly impact tumor cell evasion from immune system recognition. For instance, in glioma, uncoupling protein (UCP)2 has been proposed to link the glycolytic switch to dampened immune response [ 156 ].…”
Section: Implications For Diagnostics and Therapymentioning
confidence: 99%